Morfoanatomia e fitoquímica de Cymbopogon densiflorus (Steud.) Stapf e Cymbopogon nardus (L.) Rendle (Poaceae: Panicoideae) - Barbosa, Lília Cristina Souza (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2008)
Veja o resumo no arquivo em .pdf